Population-size history inferences from the coho salmon (Oncorhynchus kisutch) genome - Eric B Rondeau; Kris A Christensen; David R Minkley; Jong S Leong; Michelle T T Chan; Cody A Despins; Anita Mueller; Dionne Sakhrani; Carlo A Biagi; Quentin Rougemont; Eric Normandeau; Steven J M Jones; et al. (G3: Genes, Genomes, Genetics, 2023)
AbstractCoho salmon (Oncorhynchus kisutch